The Effect of Technology Use on Employability Perception - Nuh Osman Yıldız (Journal of Educational Issues, 2024)
The study aims to examine whether the use of technology has a predictive effect on the employability perceptions of university students studying in the field of sports sciences in terms of variables of gender, department and foreign language knowledge levels. The sample of this study, that aims to examine the predictive effect of the level of technology use of students studying in the field of sports sciences on their perceptions of employability, and to examine these concepts in terms of gender, department, working in the fields of sports sciences and level of foreign language knowledge, consisted of a total of 232 participants, 101 females and 131 males. In the study the “Employability Perception Scale” (EPS) developed by Rothwell et al. (2008) and adapted into Turkish by Karlı (2016), and the Technology Use Scale (TUS) developed by Zincirkıran and Tiftik (2014) were used. According to the results of the analysis, a significant difference was found in the use of technology in terms of foreign language knowledge (p < 0.05). No significant difference was determined in terms of FAI and TSK and other variables. Finally, it was determined that the use of technology had a 22% effect on the perception of employability. As a result, it is possible to state that the employability perceptions and technology use levels of the students studying in the field of sports sciences are high, and the use of technology is a significant predictor of the employability perception.